Implementation of Quality of Service and Management of Expenditure Reports in SMEs Convection Embroidery Indah Collection - Ari Soeti Yani; Indah Eka Liana (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2023)
This study aims to test and analyze the application of service quality and management of shopping reports to UMKM beautiful embroidery convection collections. This study uses data collection through observation, namely data collection trying to observe the social situation in the field. The results of this study indicate that through observation, namely data collection trying to observe the social situation in the field, the quality of service is able to satisfy the wants and needs of the community, the management of expenditure reports can be managed or recorded properly and correctly will provide business benefits and can provide development in its business. The results of this study recommend that if you want to create good MSME implementation, the priority strategy applied is to have quality service in order to create sustainable customers.